Studies on Hydration Swelling and Bound Water Type of Sodium- and Polymer-Modified Calcium Bentonite - Yong Wan; Dongdong Guo; Xinminnan Hui; Lei Liu; Yuan Yao (Advances in Polymer Technology)
Modified calcium bentonite (Ca-bentonite) is extensively used in engineered barrier systems (EBSs) for municipal and industrial disposal sites due to its high swelling potential and low hydraulic conductivity. However, few studies have focused on the micromechanism of hydration and swelling under the effect of inorganic chemical solution. In this study, free swell index (FSI) and the type and content of modified Ca-bentonite bound water under the inorganic chemical solution were quantitatively studied by using the free swell test and nuclear magnetic resonance (NMR). According to the results, modification of sodium and polymer significantly increases the FSI of Ca-bentonite, bringing it close to that of natural sodium bentonite. In addition, the chemical stability of polymer-modified bentonite is significantly higher than that of sodium-modified bentonite but less than that of natural Na-bentonite. The FSI of modified Ca-bentonite decreases with the increase of cation valence and ionic strength. T2 distribution curves of the two types of modified bentonite are three-peak curves. With the increase of ionic strength, the content of total water and permeated hydrated water (accounting for 69%–95%) in bentonite decreases gradually, whereas the surface hydration water (accounting for 2%–31%) and free water content (accounting for 0–15%) increase. A uniform linear relationship exists between the FSI and corresponding total peak area of NMR (independent of ion valence, concentration, and bentonite type). Furthermore, a linear relationship exists between the FSI of the same type of bentonite and the T2 relaxation time. Research results can provide data and theoretical basis for quantitative analysis and mechanism of the hydration swelling of bentonite.